Some Observations on Shape Factors Influencing Aerodynamic Lift on Passenger Cars - Jeff Howell; Steve Windsor; Martin Passmore (Fluids, 2021)
The car aerodynamicist developing passenger cars is primarily interested in reducing aerodynamic drag. Considerably less attention is paid to the lift characteristics except in the case of high-performance cars. Lift, however, can have an effect on both performance and stability, even at moderate speeds. In this paper, the basic shape features which affect lift and the lift distribution, as determined from the axle loads, are examined from wind tunnel tests on various small-scale bodies representing passenger cars. In most cases, the effects of yaw are also considered. The front-end shape is found to have very little effect on overall lift, although it can influence the lift distribution. The shape of the rear end of the car, however, is shown to be highly influential on the lift. The add-on components and other features can have a significant effect on the lift characteristics of real passenger cars and are briefly discussed. The increase in lift at yaw is, surprisingly, almost independent of shape, as shown for the simple bodies. This characteristic is less pronounced on real passenger cars but lift increase at yaw is shown to rise with vehicle length.